The Surface Area to Volume Ratio Changes the Pharmacokinetic and Pharmacodynamic Parameters in the Subcutaneous Tissue Cage Model: As Illustrated by Carprofen in Sheep - Munn, Richard; Whittem, Ted; Woodward, Andrew P. (Frontiers in Veterinary Science, 2022)
Introduction; Pharmacokinetic and pharmacodynamic models can be powerful tools for predicting outcomes. Many models are based on repetitive sampling of the vascular space, due to the simplicity of obtaining samples. As many drugs do not exert their effect in the vasculature, models have been developed to sample tissues outside the bloodstream. Tissue cages are hollow devices implanted subcutaneously, or elsewhere, which fill with fluid allowing reptitive sampling to occur. The physical dimensions of the cage, namely the diffusible surface area to volume ratio, would be expected to change the rate of drug movement into and out of tissue cages. Methods; Seven sheep were implanted with 5 pairs of tissue cages, subcutaneously. Each pair of cages had a different length but a fixed diffusible surface area, thus the surface area to volume ratio differed. Carrageenan was injected into half (5) of the cages in each animal during one sampling period in a cross-over design. Samples from each cage and the blood stream were obtained at 14 timepoints during two sampling periods. The concentration of carprofen was measured using LC-MS/MS and the results modelled using nonlinear mixed-effects techniques. Prostaglandin metabolites were also measured and the change over time was analysed using linear mixed effect modelling. Results; The presence of carrageenan within an animal changed the systemic pharmacokinetics of carprofen. The rate of drug movement into and out of the tissue cages varied with the surface area to volume ratio. The concentration time curve for prostaglandin metabolite changed with cage size. Conclusion; The surface area volume ratio of tissue cages will influence the calculated pharmacokinetic parameters and may affect calculated pharmacodynamics, thus it is an important factor to consider when using tissue cage data for dosing regimes.